2006
DOI: 10.1007/s11434-006-0536-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry between the upper and lower visual fields: An event-related potential study

Abstract: Using event-related potentials (ERPs), the present study examined the electrophysiological and attentional asymmetries between the upper visual field (UVF) and the lower visual field (LVF) while subjects were performing a target detecting task. The early ERP components showed a smaller P1 and a larger N1 in LVF than in UVF over the occipito-parietal areas, while the late components (N2 and P3) showed no difference between the two visual fields. In addition, the attention enhancement on the P1 component was gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…These differences suggest that there might be a LVF advantage in automatic processing of orientation contrast. Asymmetries between the UVFs and LVFs were reported in previous studies in many perceptual tasks (He et al, 1996 ; Rubin et al, 1996 ; Qu et al, 2006 ; Pourtois et al, 2008 ; Rauss et al, 2009 ; Bombeke et al, 2016 ). Previous studies also found that contrast sensitivity (Skrandies, 1985 ) and spatial resolution (Skrandies, 1987 ) in the LVF is higher than in the UVF.…”
Section: Discussionsupporting
confidence: 65%
“…These differences suggest that there might be a LVF advantage in automatic processing of orientation contrast. Asymmetries between the UVFs and LVFs were reported in previous studies in many perceptual tasks (He et al, 1996 ; Rubin et al, 1996 ; Qu et al, 2006 ; Pourtois et al, 2008 ; Rauss et al, 2009 ; Bombeke et al, 2016 ). Previous studies also found that contrast sensitivity (Skrandies, 1985 ) and spatial resolution (Skrandies, 1987 ) in the LVF is higher than in the UVF.…”
Section: Discussionsupporting
confidence: 65%
“…These different patterns of attentional modulation of MIB between UVF and LVF can be interpreted in the light of some ERP findings [29,30] . For example, Ao and his colleagues [29] indicated that attention-induced ERPs are greater in UVF than in LVF, and they thought that this means that less attention resources are needed in LVF than in UVF when completing a same task.…”
Section: Discussionmentioning
confidence: 72%
“…Nicholls concluded that the right visual field dominant was related to the left cortex. Wada further confirmed that the right visual field unilateral dominance was declined when the subjects' major hands were left hands [9]. But in this study, no significant differences were found between reaction times to the upper and lower visual fields.…”
Section: Discussionmentioning
confidence: 49%